The challenges of large-scale curriculum development: A case study of Guyana and St. Kitts and Nevis - Gregory Rodney MacKinnon; Susan Sarah Owen; Tyler MacLean; Rajkumar Sookraj (Universitas Pendidikan Indonesia, 2023)
Guyana and St. Kitts and Nevis have recently and independently undertaken large-scale enhancement of their public-school curriculum. An educational leadership consultancy has led the process using an implementation model based on feedback from country communities regarding graduation outcomes and the ensuing preparation of a Curriculum and Assessment Framework. Curriculum outcomes were based on international best practices and captured in a curriculum template premised on backward design. Using a mixed methods approach, independent researchers analyzed factors that necessarily impact the process of curriculum development. Quantitative and qualitative research feedback established challenges in the process of curriculum development. Categories of feedback arose from surveys, interviews, and focus groups. These included challenges in preparation for writing, perceived impact on the school system, and working conditions during the process of writing. Similarities and differences in the country contexts are examined and suggestions for an improved approach are recommended.